Development on the electrochemical stability and performance of symmetric supercapacitor-based proton-conducting alginate biopolymer electrolytes - A. F., Fuzlin; Diantoro, M.; Ahmad Salihin, Samsudin (Institute for Ionics, 2025)
Supercapacitors have emerged as advanced energy storage solutions, characterized by their rapid charge–discharge abilities, elevated power density, and remarkable cycling stability. This study focuses on improving electrochemical performance of proton-conducting alginate-based biopolymer electrolytes (BBPEs) through the addition of glycolic acid (GA) and ethylene carbonate (EC) as plasticizers for potential application in symmetric supercapacitors. Two distinct systems were developed: System I, composed of alginate with GA, and System II, which further includes ethylene carbonate EC as a plasticizer. The plasticized system demonstrated a notable improvement in ionic conductivity, which led to enhanced electrochemical properties, such as a stable potential window of 1.85 V and excellent cycling stability over 10,000 cycles. The fabricated supercapacitors for System II exhibited a specific capacitance of 19.05 F g−1 and energy density of ~ 6.20 Wh kg−1, with a power density of ~ 212 W kg−1. These findings highlight the potential of alginate-based BBPEs for use in sustainable and efficient energy storage applications.